QTL Mapping linked to downy mildew resistance genes in maize (Zea mays) - Muh Dzulkifly Ashan; MIFTAHUDIN MIFTAHUDIN; REFLINUR REFLINUR; MARCIA B. PABENDON; SIGIT BUDI SANTOSO; AGUS SALIM (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ashan MD, Miftahudin, Reflinur, Pabendon MB, Santoso SB, Salim A. 2020. QTL Mapping linked to downy mildew resistance genes in maize (Zea mays). Biodiversitas 21: 3735-3743. Downy Mildew (DM) caused by Peronosclerospora spp. is one of the most destructive diseases and problems in yield losses of maize production worldwide. Identification of molecular marker-linked to the DM resistance genes is considered as an important step in the improvement of the DM resistance nature in maize breeding program. The objective of the study was to identify molecular markers linked to the DM resistance genes in maize. A total of 198 F3 maize lines generated from a cross between R10-4430 and Kandora was used in microsatellite genetic map construction and the corresponding F3: 4 families were used in phenotypic evaluation to identify quantitative trait loci (QTLs) responsible for DM resistance-related trait. The entire genetic linkage map constructed with 28 SSR markers resulted in 460.3 cM with an average distance between markers of 26.85 cM. Seven main-effect QTLs controlling the DM resistance genes were identified in the entire genome map of F3 population with the phenotypic variation explained (PVE) values ranged from 43.35 to 53.71%. Among detected QTLs, three QTLs, qDM-Pp1a, qDM-Pp1b1, and qDM-Pp1b2 were detected on chromosome 1, one QTL, qDM-Pp5 was on chromosome 5, two QTLs, qDM-Pp6b1 and qDM-Pp6b2 were on chromosome 6 and one QTL, qDM-Pp10 was on chromosome 10. The effect of detected QTLs responsible for DM resistance trait ranged from 43.35 to 53.71% and those will be potential to be further used as molecular aided selection in maize breeding for DM resistance.